2018
DOI: 10.1007/s00425-018-2987-6
|View full text |Cite
|
Sign up to set email alerts
|

Tomato MYB49 enhances resistance to Phytophthora infestans and tolerance to water deficit and salt stress

Abstract: MYB49-overexpressing tomato plants showed significant resistance to Phytophthora infestans and tolerance to drought and salt stresses. This finding reveals the potential application of tomato MYB49 in future molecular breeding. Biotic and abiotic stresses severely reduce the productivity of tomato worldwide. Therefore, it is necessary to find key genes to simultaneously improve plant resistance to pathogens and tolerance to various abiotic stresses. In this study, based on homologous relationships with Arabido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 74 publications
3
53
0
Order By: Relevance
“…Additionally, the enzyme activities of POD and SOD were significantly lower in the L1-L3 plants than in the WT plants upon infection ( Figure 4B, C). This was consistent with the notably decreased expression of SlSOD and SlPOD (genes encoding the SOD and POD enzymes in tomato) [20,35]. in the L1-L3 plants compared with the WT plants upon infection ( Figure 4D, E).…”
Section: Overexpression Of Mir482c Contributed To Changes In Physiolosupporting
confidence: 82%
See 2 more Smart Citations
“…Additionally, the enzyme activities of POD and SOD were significantly lower in the L1-L3 plants than in the WT plants upon infection ( Figure 4B, C). This was consistent with the notably decreased expression of SlSOD and SlPOD (genes encoding the SOD and POD enzymes in tomato) [20,35]. in the L1-L3 plants compared with the WT plants upon infection ( Figure 4D, E).…”
Section: Overexpression Of Mir482c Contributed To Changes In Physiolosupporting
confidence: 82%
“…strain "GV3101" by the freeze-thaw method [35]. The culture of A. tumefaciens was centrifuged for 10 min at 4000 × g, and the pellet was resuspended in infiltration medium (10 mM MES, 10 mM MgCl2, and 20 µM acetosyringone; OD600 = 1.0).…”
Section: Transient Overexpression Of Mir482c In Tomatomentioning
confidence: 99%
See 1 more Smart Citation
“…The members of the MYB and NAC families can be mediators in both the increased synthesis of AtMSRB9 proteins during dehydration stress [15] and the upregulation of PMSRA4 under oxidative stress conditions [13], because the PMSR4 promoter contains 34 binding sites for MYB-type TFs and 17 binding sites for NAC-type TFs. Similarly, the promoter of AtMsrB9 contains 42 binding sites for MYB-type TFs, including binding sites for MYB49, MYB52, and MYB96, which act under water stress [62,63,64], and 35 binding sites for NAC-type TFs, including dehydration-related NAC096 [65]. The NAC-type TFs IDEF1/IDEF2, which are similar to MYB58 [66], are linked to iron deficiency in plants [67].…”
Section: Discussionmentioning
confidence: 99%
“…A previous research project reported that GmMYB118 could improve tolerance 82 to drought and salt stress in soybean plants through promoting expression of stress-associated 83 genes and regulating osmotic and oxidizing substances to maintain cell homeostasis (Du et al, 84 2018). Furthermore, overexpression of another gene, MYB49, in tomato plants was associated 85 with significant tolerance to drought and salt stresses (Cui et al, 2018). Therefore, the MYB 86 gene family acts as an important transcription factor to improve plant resistance to abiotic stress.…”
mentioning
confidence: 99%